MARKETING STRATEGY FOR PURCHASE INTEREST AT DENASA WATER DEPOT - Febri Nadia Syaputri; Dewi Shinta Wulandari (SEAN Institute, 2023)
This research was conducted at the Denasa water Refillable Drinking Water Depot located on Jalan Air Bersih Gg sederek Sudirejo 1 Medan city. The purpose of this study is to reveal the successful sales strategy used by Denasa Water's Refillable Drinking Water Depot business in maintaining its business. This research uses qualitative methods with a case study approach. The types of data used in this study are primary data and secondary data. Data collection techniques using interviews, and observation of Informant Selection in this study revealed 6 people, namely 2 Business Owners, 2 Employees, and 2 Consumers. The results of this study show that the success of Denasa Water Refill Drinking Water Depot in maintaining its business is supported by several aspects. Among them are quality products, responsive service, affordable prices, massive sales promotions, superior quality, friendly service. This is the key to Success